White blood cell estimates correlate to measures of population and individual health in an endangered population of Marbled Murrelets (Brachyramphus marmoratus) - Ryan, Kelsey; Adrean, Lindsay J.; Betts, Matt G.; Dachenhaus, Jonathan; Johns, Jennifer; Michlanski, Miranda; Nelson, S. Kim; Phelps, Shannon; Rivers, James W.; Roby, Daniel D.; Woodis, Ethan; Beechler, Brianna R. (Frontiers in Veterinary Science, 2025)
IntroductionEstimated white blood cell (WBC) counts are a valuable tool for assessing individual and population health in wildlife and domestic animals due to their role in the response to environmental stressors and disease. These measures are infrequently used in the study of wild seabird species, despite their utility when used alongside other common health assays - such as infectious disease testing, body condition, and population monitoring efforts. The Marbled Murrelet (Brachyramphus marmoratus) is a seabird of conservation concern that is federally listed as threatened by the states of Oregon, Washington, and California, thus necessitating the evaluation of its physiological health.MethodsWe evaluated the utility of estimated WBC counts as measures of health, asking whether counts changed by measures of individual health (i.e., sex, L. marmoratii hemoparasite burden, body condition index, and nesting propensity) and population health (i.e., changes in counts by year). We used blood smears collected from over 350 murrelets captured along the Oregon Coast between April and June of 2017-2019 and 2021-2022 to estimate total WBC and differential counts.ResultsEstimated WBC counts were found to appear lower in years with more favorable ocean conditions, when nesting propensity was relatively high. Male murrelets, individuals less likely to nest, and individuals with greater L. marmoratii burden had significantly lower estimated WBC counts, whereas individuals with a lower body condition index had elevated estimated WBC counts.DiscussionThese results demonstrate the utility of estimated WBC counts to further assess health at the individual and population levels in the study of species of heightened conservation concern and should be considered as an addition to research plans.